(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
currently, the global population is growing, which naturally leads to a significant increase in energy demand. There are many advantages to providing buildings with green renewable energy. The main content of the article is about the advantages of using efficient and renewable energy sources in buildings.